Espaço hedônico: convergências utópicas entre a economia solidária e o Turismo Rural - Araújo, Alessandro Faria (2024)
This thesis investigates the intersection between solidarity economy and the rurality of leisure, exploring their sociotechnological and utopian convergences, with a focus on rural tourism and solidarity economy projects, such as initiatives in Western Paraná and intercontinental efforts, including Sibateando, rural parishes, volunteer tourism, and terrace adoption. Starting from conceptual foundations like solidarity and rurality, the study analyzes the relationship between utopia and rurality, drawing on mythological and literary references such as the Enuma Elish, Hesiod's Works and Days, and Virgil's Eclogues and Georgics, as well as thinkers like Polanyi, Thomas More, Owen, and Kautsky, who discuss utopia as a "missing reality." The research also addresses the concept of hedonic space and locus amoenus, connecting it to Sustainable Rural Development (SRD) and Community-Based Tourism (CBT), proposing reflections on the construction of spaces of pleasure and well-being in rural contexts. The results highlight the feasibility and impacts of solidarity economy and rural tourism practices, pointing to the need for policies that integrate these concepts as tools for sustainable development and the promotion of rurality. It concludes that the convergence between solidarity economy and the rurality of leisure offers promising pathways for more just and sustainable societies, aligned with utopian and hedonic principles.